Assessment of the impact of hydrolysis on bound sulfonamide residue determination in honey using stable isotope dilution ultrahigh performance liquid chromatography tandem mass spectrometry. (1st November 2021) - Zhang, Yan; Li, Xiu Qin; Guo, Zhen; Zhou, Xia; Li, Shuang Qing; Li, Xiao Min; Jiao, Hui; Zhang, Qing He
Graphical abstract: Highlights: The qualitative identification of sugar-bound sulfonamides (SAs) in honey was carried out by LC-HRMS, which provides a basis for monitoring the conjugates in honey. The binding reaction rule between the sulfonamides and sugar in honey was clarified by simultaneous determination of free SAs and sugar-bound SAs. The impact of hydrolysis on the determination of bound sulfonamides in honey was quantitatively assessed by LC-MS/MS on the basis of positive samples which can simulate the naturally incurred honey. An accurate analytical method based on isotope dilution-liquid chromatography tandem mass spectrometry was developed as a candidate reference method for the determination of sulfonamides in honey. Abstract: In this study, an analytical method based on isotope dilution-liquid chromatography tandem mass spectrometry (ID-LC-MS/MS) was developed as a candidate reference method for the determination of sulfonamides (SAs) in honey. To guarantee the accuracy and authenticity, the impact of hydrolysis on bound SA residues was first investigated by enabling (i) identification of sugar-bound SAs, (ii) clarifying the binding reaction rule between the SAs and sugar, (iii) detection of free SAs and sugar-bound SAs, and (iv) preparation of SA-contaminated honey. Thus, the efficiency of different hydrolysis conditions was assessed by comparing the bound SA content before and after hydrolysis. In addition, optimization of the sample pretreatment procedures and LC conditions to minimize matrix effects by separation from significant matrix interferences was also performed. Satisfactory results in terms of hydrolysis efficiency (approximately 88.3%–99.2%), extraction efficiency (84.2%–105.3%), recovery (95.9%–103.1%), and limit of quantification (0.6–1.5 μg·kg −1 ) were obtained.